please solve this question
please
Attachments:
![](https://hi-static.z-dn.net/files/d29/8622e701673b59e10c9cfcad3d93bebe.jpg)
Answers
Answered by
2
Step-by-step explanation:
(1+tanAtanB)²+(tanA-tanB)²
=1+tan²Atan²B+2tanAtanB+tan²A+tan²B-2tanAtanB
=1+tan²A+tan²Atan²B+tan²B
=sec²A+tan²B(1+tan²A)
=sec²A+tan²Bsec²A
=sec²A(1+tan²B)
=sec²Asec²B
Attachments:
![](https://hi-static.z-dn.net/files/dfb/593fb50a5d5b5bc5dbe06a26600d079c.jpg)
Answered by
0
(1+tanAtanB)²+(tanA-tanB)²
=1+tan²Atan²B+2tanAtanB+tan²A+tan²B-2tanAtanB
=1+tan²A+tan²Atan²B+tan²B
=sec²A+tan²B(1+tan²A)
=sec²A+tan²Bsec²A
=sec²A(1+tan²B)
=sec²Asec²B
Similar questions